Prevalence of mood and substance use disorders among patients seeking primary care office-based buprenorphine/naloxone treatment. - Savant, Jonathan D; Barry, Declan T; Cutter, Christopher J; Joy, Michelle T; Dinh, An; Schottenfeld, Richard S; Fiellin, David A (Drug and alcohol dependence, 2012)
BACKGROUND: Psychiatric comorbidity can adversely affect opioid dependence treatment outcomes. While the prevalence of psychiatric comorbidity among patients seeking methadone maintenance treatment has been documented, the extent to which these findings extend to patients seeking primary care office-based buprenorphine/naloxone treatment is unclear. AIMS: To determine the prevalence of mood and substance use disorders among patients seeking primary care office-based buprenorphine/naloxone treatment, via cross sectional survey. METHODS: 237 consecutive patients seeking primary care office-based buprenorphine/naloxone treatment were evaluated using modules from the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I). Current (past 30days) and past diagnoses were cataloged separately. RESULTS: Patients ranged in age from 18 to 62years old (M=33.9, SD=9.9); 173 (73%) were men; 197 (83%) were white. Major depression was the most prevalent mood disorder (19% current, 24% past). A minority of patients met criteria for current dysthymia (6%), past mania (1%), or past hypomania (2%). While 37 patients (16%) met criteria for current abuse of or dependence on at least one non-opioid substance (7% cocaine, 4% alcohol, 4% cannabis, 2% sedatives, 0.4% stimulants, 0.4% polydrug), 168 patients (70%) percent met criteria for past abuse of or dependence on at least one non-opioid substance (43% alcohol, 38% cannabis, 30% cocaine, 9% sedatives, 8% hallucinogens, 4% stimulants, 1% polydrug, and 0.4% other substances). CONCLUSION: Mood and substance use comorbidity is prevalent among patients seeking primary care office-based buprenorphine/naloxone treatment. The findings support the need for clinicians to assess and address these conditions.